Analisis Pengaruh Sektor Keuangan terhadap Inflasi di Indonesia - Andini, Natasya Putri; Pasaribu, Esti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
This research aims to determine the influence of the Indonesian financial sector on inflation. The research used data collected from secondary sources, such as Bank Indonesia, the Federal Reserve Bank of St. Louis, and Investing.com. The independent variables in this study were the Composite Stock Price Index, JIBOR, and bond yield, while the dependent variable included inflation. Vector Autoregression (VAR) or Vector Error Correction Model (VECM) was employed as the research method. The findings showed that inflation was positively and significantly impacted by the Composite Stock Price Index over the long run. Conversely, JIBOR significantly and negatively impacted inflation over the long run. In contrast, bond yield had no effect on inflation. Overall, inflation was positively and significantly affected by the Composite Stock Price Index, JIBOR, and bond yield when considering the short term.